Particulate Air Pollution and Impaired Maternal Lung Function in Ndola And Masaiti of Copperbelt Province in Zambia - Mulenga, David; Zulu, Mbawe (European Journal of Applied Sciences, 2022)
Background Evidence of association between maternal indoor air pollution (IAP) exposure and impaired lung function (LF) in sub-Saharan Africa (SSA) is insufficient. We assessed association between maternal IAP and impaired LF in Masaiti and Ndola. Method The study used questionnaire to collect data (N =1170) and IAP exposure defined as use of biomass fuel indoors and elevated PM2.5 using foobot (China) and LFs using a spirometer (Spirobank G, Italy). Data were analysed using SPSS version 20. Results Results indicated an association between fuel use and lung function result. The median (Q1, Q3) PM2.5 before, during and after cooking showed a significant difference (p value <0.001). The median (Q1, Q2) PM2.5 during cooking and daily average were 501(411, 686) µg/m3 and 393 (303,578) µg/m3. Association between PM2.5 and fuel type (p value = 0.005) but no association between PM2.5 and kitchen type (p value = 0.124). Association between fuel type and impaired lung function. Compared with combined fuel types (Charcoal and electricity), crop residue only, gave 2times more likely to have a declined lung function [AOR: 2.33 (1.27 – 4.30] and electricity only, 57% less likely to have declined lung function [AOR: 0.43, 95% CI (0.26 – 0.69)]. Conclusion Maternal IAP exposure maybe associated with elevated risk of impaired LFs. More research using longitunal studies carefully designed for low income countries is needed. Public awareness of the effects of IAP due to biomass fuels and interventions to reduce the use of biomass fuels are required.